Respuesta :

Answer:

Step-by-step explanation:

4). By applying cosine rule for angle R,

    cos(∠R) = [tex]\frac{\text{Adjacent side}}{\text{Hypotenuse}}[/tex]

    cos(33°) = [tex]\frac{x}{19}[/tex] [Equation]

    x = 19cos(33°)

       = 8.39

5). By applying sine rule,

    cos(20°) = [tex]\frac{\text{Opposite side}}{\text{Hypotenuse}}[/tex]

    cos(20°) = [tex]\frac{15}{x}[/tex] [Equation]

    x = [tex]\frac{15}{\text{cos}20}[/tex]

    x = 15.96

6). By applying tangent rule,

    tan(40°) = [tex]\frac{\text{Opposite side}}{\text{Adjacent side}}[/tex]

    tan(40°) = [tex]\frac{15}{x}[/tex] [Equation]

     x = [tex]\frac{15}{\text{tan}40}[/tex]

     x = 17.88

ACCESS MORE